Analysis Of Paint Material Requirements in the S-80 Tugboat Hull Painting Project - Riandika Putra Rama; Intan Baroroh; Ali Azhar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Calculating the paint requirements is a lengthy and meticulous process. Therefore, the company needs to calculate the painting requirements correctly and accurately. The painting process is one of the processes in shipbuilding. The coating process involves painting or layering ship steel plates with special paint to protect the vessel. This research aims to estimate the material and cost requirements for the S-80 tugboat construction project by calculating the needs, coating with 2 different products so that a comparison of materials and costs can be made, namely International and Nippon Paint. The amount of paint needed is determined based on the surface area of the underwater and topside hull of a 26-meter tugboat. This study applies a quantitative method, so resulting in final outcomes presented in numerical form. According the research, he total coating needs for the hull of the ship for the bottom part using the International brand is 111,6 L and for the Top Side is 59,43 L, while for the Nippon Paint brand, the Bottom part is 64,5 L and the Top Side is 57,6 L. For the coating process, the total cost for the bottom and topside areas with the International brand amounts to Rp31.702.000. Meanwhile, for the Nippon Paint brand, the cost for the bottom and topside areas is Rp11.238.000 in total.